Use of virtual simulators in the teaching of Nursing: scoping review (Research, Society and Development, 2021)
The use of virtual simulation can offer a safe and quality environment for the development of essential skills of nursing students, during the clinical decision-making process. The general objective was to identify the scientific production on the use of virtual simulators in nursing education. This is a scoping review, carried out on the Web of Science, Scopus, Pubmed/Medline, SciELO e BDENF, in the period from 2005 to 2020. The sample consisted of 14 articles. The analysis allowed to identify the prevalence of studies in the areas of child health and patient safety, and the use of “Simulation - virtual patient”. Virtual simulators can contribute to the teaching of nursing, as they can help the student to practice the knowledge of theory, clinical experiences, or that can assist in the development of critical thinking.